Physiological responses and match characteristics in professional tennis players during a one-hour simulated tennis match - Kilit, B.; Senel, Ö.; Arslan, E.; Can, S. (Journal of Human Kinetics, 2016)
The purpose of this study was to investigate the effects of serve and return game situations on physiological responses and match characteristics in professional male tennis players during one hour-long simulated singles tennis matches. Ten internationally ranked tennis players (age 22.2 ± 2.8 years; body height 180.7 ± 4.4 cm; body mass 75.9 ± 8.9 kg) participated in this study. Their physiological responses were measured using two portable analyzers during indoor hard court matches. Ratings of perceived exertion were also determined at the end of the game. The variables describing the characteristics of the matches determined from video recordings were: (a) duration of rallies; (b) rest time; (c) work-to-rest ratio; (d) effective playing time; and (d) strokes per rally. Significant differences (p<0.05) were found between serving and returning conditions in an hour-long simulated singles tennis match in terms of oxygen uptake, a heart rate, ratings of perceived exertion, pulmonary ventilation, respiration frequency and a respiratory gas exchange ratio. In addition, both the heart rate and ratings of perceived exertion responses were moderately correlated with the duration of rallies and strokes per rally (r = 0.60 to 0.26; p<0.05). Taken together, these results indicate that the serve game situation has a significant effect on the physiological response in an hour-long simulated tennis match between professional male tennis players. These findings might be used for the physiological adaptations required for tennis-specific aerobic endurance.